Integrated Multi-view 3D Image Capture and Motion Parallax 3D Display System - Madan Lal; Shadi Khan Baloch; Shoaib Rehman Soomro (EMITTER International Journal of Engineering Technology, 2022)
We propose an integrated 3D image capture and display system using a transversely moving camera, regular 2D display screen and user tracking that can facilitate the multi-view capture of a real scene or object and display the captured perspective views in 3D. The motion parallax 3D technique is used to capture the depth information of the object and display the corresponding views to the user using head tracking. The system is composed of two parts, the first part consists of a horizontally moving camera interfaced with a customized camera control and capture application. The second part consist of a regular LCD screen combined with web camera and user tracking application. The 3D multi-view images captured through the imaging setup are relayed to the display based on the user location and corresponding view is dynamically displayed on the screen based on the viewing angle of the user with respect to the screen. The developed prototype system provides the multi-view capture of 60 views with the step size of 1 cm and greater than 40˚ field-of-view overlap. The display system relays 60 views providing the viewing angle coverage of ±35˚ where the angular difference between two views is 1.2˚.